“No inicio tive uma sensação de medo”: o exercício da docência em um ambiente socioeducativo – trajetórias de vida-formação-docência - Fernando Miranda Arraz (2022)
Carrying out a research with the theme of teaching performance in an environment of deprivation of liberty is not a simple task, because in addition to involving the school reality, it also involves a safe environment with all its particularities. This study deals with the teaching practice within a socio-educational unit of provisional detention. This research aims to analyze, through life-training-teaching stories, the meanings of the experiences attributed by teachers who work in a socio-educational environment of provisional detention with adolescents/young people who are deprived of liberty. In this study, education is considered as a practice of freedom, also recognized as a political act of awareness and humanization (Freire, 2007, 1999, 1997). Studies by Tardif (2016), Gauthier et. al (2006 and 2013) and Perrenoud (1999 and 2002) helped us to think of teaching practice as an interactive work in which the investigation of teaching action is essential for recognizing the importance of the teacher's role. To discuss teaching in deprivation of liberty environments, we base ourselves on studies by Onofre (2013) and Silva (2017). This study is anchored in (auto)biographical Research, since those who narrate their own lives, by narrating, establish relationships of temporality and situations with themselves and with those with whom they interact, enabling teachers to position themselves in relation to their life-training trajectories -teaching. We used the Narrative Interview (EN) as a data production device, which proposes a moment of self-reflection, when the story of life-training-teaching begins to re-signify itself, bringing to light through the language itself and, through it, processing again the lived experiences, as a chance to answer for themselves. To understand the research sources, we based ourselves on Souza (2014) through the understanding-interpretation in three phases: time to remember, narrate and reflect on the experience, understanding what he calls pre-analysis, thematic reading and interpretive reading. Through the narratives, the teaching profession, in this space of deprivation of liberty, assumes the challenge of making the teenager who is cautious, able to realize that his learning is, beyond the rigid, cold and contradictory architecture imposed by imprisonment, intertwined with a more solid and critical education, aiming at a liberating education. As an educational resource, we developed an Extension Project in partnership with the LapenSi Research Group based on (auto)biographical Research, providing a space for discussion, production and socialization of Teaching Cases, highlighting the training and teaching experiences of teachers and of future teachers, at different levels, teaching modalities and contexts, debating the initial training of teachers, the exercise of teaching in different contexts and their pedagogical practices and discussions about educational policies.